Post Feminism Value In “Tinker Bell” Film (The Pirate Fairy 2014) - Lakoro, Moh. Mustakin; Podungge, Rusni; Usu, Novi Rusnarty (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the representation of postfeminist values in the 2014 animated film Tinker Bell and the Pirate Fairy. The objective is to explore how the film’s dialogues portray postfeminist values through the characters and narrative. Using a descriptive qualitative method and feminist literary criticism, the study applies the postfeminist theoretical framework proposed by Rosalind Gill. The analysis focuses on five key values: empowerment, individualism and choice, redefinition of gender roles, collaboration and solidarity, and resistance to patriarchal structures. The findings reveal that the film presents female characters, especially Zarina and Tinker Bell, as intelligent, independent, and emotionally expressive figures who challenge traditional gender norms. However, the representation of empowerment remains tied to neoliberal ideals, where success is achieved through personal effort rather than structural change. This research contributes to feminist media analysis and offers insight into how children’s animated films embed ideological messages about gender and identity.